Male Rat Genital Tract Infection With Chlamydia Muridarum has No Significant Consequence on Male Fertility - Motrich, Ruben Dario (2012)
Purpose: Chlamydia trachomatis infection of the male genital tract was proposed to alter male fertility. We studied the putative consequences of chlamydial male genital tract infection on semen quality and male fertility in an experimental rat model of infection. Materials and Methods: We used 36 male and 40 female Wistar rats. Male genital infection was created by inoculating Chlamydia muridarum in the meatal urethra. The presence of C. muridarum was evaluated by polymerase chain reaction in semen and male genital tract organs early (15 days) and late (80 days) after infection. Sperm quality parameters were assayed in seminal and epididymal sperm from sham infected and infected rats. Mating studies with sexually mature females were performed and fertility parameters were assayed, including potency, fecundity and fertility indexes, fetal size, and pre-implantation and post-implantation embryo loss. Results: Male rats showed ascending, disseminated infection 15 days after infection. Bacteria persisted in the prostate and seminal vesicles 80 days after infection. C. muridarum was detected in semen in most rats regardless of acute or chronic infection. Seminal or epididymal sperm quality did not differ in infected and sham infected rats 15 or 80 days after infection. Sperm apoptosis was also minimal in infected rats. No differences were observed in fertility parameters between infected and sham infected rats. Conclusions: C. muridarum infects the rat male genital tract and persists mainly in the prostate. Although C. muridarum was detected in semen during acute and chronic infection, no alterations in sperm quality were observed. C. muridarum infection does not impair male fertility.